2021
DOI: 10.1002/sctm.20-0534
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells and Three-Dimensional-Osteoconductive Scaffold Regenerate Calvarial Bone in Critical Size Defects in Swine

Abstract: Craniofacial bones protect vital organs, perform important physiological functions, and shape facial identity. Critical-size defects (CSDs) in calvarial bones, which will not heal spontaneously, are caused by trauma, congenital defects, or tumor resections.They pose a great challenge for patients and physicians, and significantly compromise

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…The regeneration process of MSCs involves two potential mechanisms: direct proliferation or differentiation and indirect paracrine function [ 50 , 51 ]. MSCs can proliferate as undifferentiated stem cells and differentiate into various lineages, depending on the microenvironment, with the replacement of loose endogenous cells and damaged tissues [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regeneration process of MSCs involves two potential mechanisms: direct proliferation or differentiation and indirect paracrine function [ 50 , 51 ]. MSCs can proliferate as undifferentiated stem cells and differentiate into various lineages, depending on the microenvironment, with the replacement of loose endogenous cells and damaged tissues [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The regeneration process of MSCs involves two potential mechanisms: direct proliferation or differentiation and indirect paracrine function [ 50 , 51 ]. MSCs can proliferate as undifferentiated stem cells and differentiate into various lineages, depending on the microenvironment, with the replacement of loose endogenous cells and damaged tissues [ 51 ]. Moreover, the secretion of bioactive soluble factors and extracellular vesicles (including exosomes and microRNAs) through their paracrine effects of MSCs support the survival of endogenous cells and the improvement of the microenvironment by modulating the angiogenesis, osteogenesis, and immune responses; suppressing apoptosis; reducing oxidative stress; and recruiting tissue-specific progenitor cells [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…As with hydroxyapatite, the incorporation of tricalcium phosphate with other scaffold materials has been extensively investigated [ 165 ]. In vitro work by Park et al demonstrated the effects of a β-TCP/polycaprolactone (PCL) scaffold on human adipose and bone marrow derived stem cells, in which the scaffolds promoted significantly higher osteogenic differentiation, gene expression, and levels of ossification proteins compared to negative controls [ 166 ].…”
Section: Future Directions For Addressing Bone Lossmentioning
confidence: 99%
“…The high‐purity MSCs can be derived from hESCs with the limited passage and good osteogenic ability 14 . However, MSCs alone are insufficient for bone regeneration; generally, they are combined with scaffolds of appropriate shape, size and mechanical properties, in treatment 15,16 …”
Section: Introductionmentioning
confidence: 99%
“…14 However, MSCs alone are insufficient for bone regeneration; generally, they are combined with scaffolds of appropriate shape, size and mechanical properties, in treatment. 15,16 Microcarriers are often considered suitable as spherical scaffolds for cell culture, growth and delivery. 17 Porous microcarriers are widely used in tissue engineering due to their benefits in offering large surface area for cell growth, maintaining differentiated cell phenotypes and facilitating injection into target sites for repair or regeneration.…”
mentioning
confidence: 99%